Determining electrical losses of the traction drive of electric train based on a synchronous motor with excitation from permanent magnets - Liubarskyi, Borys; Demydov, Aleksandr; Yeritsyan, Bagish; Nuriiev, Ramil; Iakunin, Dmytro (Eastern-European Journal of Enterprise Technologies, 2018)
We have studied a traction drive based on the synchronous motor with excitation from permanent magnets for its electrical losses. A simulation model of the traction drive is synthesized, which employs the algorithm of a space-vector PWM. A special feature of the model is the application of parameters of actual IGBT-transistors and the possibility for obtaining instantaneous values of electric losses in transistors and snubbers of the inverter under different modes of operation. We have devised a procedure for calculating electric losses in the traction engine based on the shape of phase currents, geometrical and electrical parameters of the engine. Simulation of the traction drive and calculation of losses in the traction engine is integrated, which makes it possible to account for the impact of the inverter and engine on each other. We have simulated work of the reducer-free traction drive based on a synchronous motor with excitation from permanent magnets with a capacity of 80 kW. The dependences were constructed for losses in the traction inverter and engine on the clock frequency of a space-vector PWM and motion speed. The proposed procedure makes it possible to quantify the magnitude of electric losses in the traction drive elements depending on the types of transistors applied, clock frequency of the inverter, and parameters of the engine. This enables the optimization of the traction drive for the criterion of maximum performance efficiency, as well as thermal calculation of the elements of the drive.